1990
DOI: 10.1029/jb095ib07p10929
|View full text |Cite
|
Sign up to set email alerts
|

The electrical conductivity distribution beneath Vancouver Island: A region of active plate subduction

Abstract: Magnetotelluric (MT) and geomagnetic depth sounding (GDS) data were recorded at 25 locations across Vancouver Island, Canada, over the subducting Juan de Fuca plate. The GDS data respond to a number of local conductive features at frequencies above 10 Hz while at longer periods, the in-phase and quadrature induction arrows axe colineax and are aligned approximately normal to the continental shelf with a maximum amplitude response neax the southwest coast. Interpretation of the MT data show the presence of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 69 publications
3
49
0
Order By: Relevance
“…A lower crustal conductor beneath the aseismic front to the west in northeastern Japan has suggested the presence of H2O (e.g., Utada, 1987). Beneath the Oregon coast and Vancouver Island in North America, a high conductivity layer on the top of the descending Juan de Fuca plate has been observed, and lends itself to the inference of H2O-charged sediments that are partially subducted with the oceanic crust (e.g., Wannamaker et al, 1989;Young and Kitchen, 1989;Kurtz et al, 1990). A similar conductive layer has also been proposed in the Japan arc subduction zone by Utada (1987 …”
Section: Comparison With Heat Flow Temperaturementioning
confidence: 70%
“…A lower crustal conductor beneath the aseismic front to the west in northeastern Japan has suggested the presence of H2O (e.g., Utada, 1987). Beneath the Oregon coast and Vancouver Island in North America, a high conductivity layer on the top of the descending Juan de Fuca plate has been observed, and lends itself to the inference of H2O-charged sediments that are partially subducted with the oceanic crust (e.g., Wannamaker et al, 1989;Young and Kitchen, 1989;Kurtz et al, 1990). A similar conductive layer has also been proposed in the Japan arc subduction zone by Utada (1987 …”
Section: Comparison With Heat Flow Temperaturementioning
confidence: 70%
“…The experiment transect intersects the rifted marginal Otway basin, which is a few kilometres wide and deep (Williams and Corliss, 1982;Finlayson et al, 1994). The effect of brinesaturated sediments on the coast effect at subduction zones has been discussed by Kurtz et al (1986Kurtz et al ( , 1990 and Wannamaker et al (1989), but has not been observed at passive margins. For example, the models of White et al (1990) and Kellett et al (1991) for southeastern Australia gave a good fit of the observed data without the presence of sediment beneath the continental shelf and slope.…”
Section: Tectonic Interpretationmentioning
confidence: 99%
“…Thermal structure and chemical composition may lead to lateral variations in conductivity across the coastlines. At active continental margins in northwestern USA (Kurtz et al, 1986(Kurtz et al, , 1990Wannamaker et al, 1989) and Japan (Ogawa et al,1986) the subduction of fluids gives rise to a very marked lateral variation in upper mantle conductivity across the margin, but at passive margins there is less obvious reason for such a difference. In Fig.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetotelluric survey and modeling (Kurtz et al, 1986(Kurtz et al, , 1990) revealed a landward dipping highly conductive zone in the 20-50 km depth range beneath southern Vancouver Island. The high conductivity zone was originally interpreted as the subducted oceanic crust but later recognized to be in the lower crust and mantle wedge above the slab.…”
Section: Introductionmentioning
confidence: 99%